Development of an Educational Program to Increase Cultural Awareness and Tourism Ethics in Puri Gede Kaba Kaba - Sudiarta, I Nyoman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to determine the development of educational programs that can increase cultural awareness and tourism ethics in Puri Gede Kaba-Kaba. The qualitative research method focuses on collecting data through observation, interviews, and documentation of thoughts to gain an in-depth understanding of the research subject. Through the Milles and Huberman data analysis method, this research identified implied meanings and comprehensive categorization of data, which was then interpreted to reveal relationships between categories. The research results show that the educational program developed successfully integrates the concept of Eudaimonia, Kant's deontological view, and Kohlberg's theory of moral development in character education. The program effectively teaches respect for local culture, environmental responsibility, and social awareness and contributes to preserving cultural heritage and the environment. This research concludes that comprehensive character education can improve moral character and wise decision-making among tourism actors and visitors, with direct implications for increasing the positive benefits of the tourism industry for local communities. The implications of this research also include recommendations for implementing similar educational programs in other tourism locations, involving more comprehensive collaboration with educational institutions and using social media to promote and evaluate tourism culture and ethics education activities.